Exploration of risk taking behaviors and perceived susceptibility of colorectal cancer among Malaysian adults: a community based cross-sectional study - Al-Dubai, S.A.R.; Ganasegaran, K.; Al-Absi, A.M.; Shah, S.A.; Razali, F.M.M.; Arokiasamy, J.T. (BioMed Central, 2013)
Background: Perceived susceptibility to an illness has been shown to affect Health-risk behavior. The objective of the present study was to determine the risk taking behaviors and the demographic predictors of perceived susceptibility to colorectal cancer in a population-based sample. Methods: A cross-sectional study was carried out among 305 Malaysian adults in six major districts, selected from urban, semi-urban, and rural settings in one state in Malaysia. A self-administered questionnaire was used in this study. It was comprised of socio-demographics, risk-taking behaviors, and validated domains of the Health Belief Model (HBM). Results: The mean (+/- SD) age of the respondents was 34.5 (+/- 9.6) and the majority (59.0%) of them were 30 years or older. Almost 20.7% of the respondents felt they were susceptible to colorectal cancer. Self-reported perceived susceptibility mirrored unsatisfactory screening behaviors owing to the lack of doctors' recommendation, ignorance of screening modalities, procrastination, and the perception that screening was unnecessary. Factors significantly associated with perceived susceptibility to colorectal cancer were gender (OR = 1.8, 95% CI 1.0-3.3), age (OR = 2. 2, 95% CI 1.2-4.0), ethnicity (OR = 0. 3, 95% CI 0.2-0.6), family history of colorectal cancer (OR = 3. 2, 95% CI 1.4-7.4) and alcohol intake (OR = 3.9, 95% CI 2.1-7.5). Conclusion: The present study revealed that screening behavior among respondents was unsatisfactory. Hence, awareness of the importance of screening to prevent colorectal cancers is imperative.